Training and Assistance in Making Healthy Drink for Heartburn Reliever - Wibowo, Teguh Setiawan; Hidayati, Nurul; Mubarokah, Fitroh Annisaul (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of the training and assistance activities in making healthy drinks to relieve heartburn are to provide knowledge, skills to individuals or groups and provide solutions regarding healthy drinks to relieve heartburn that are good to drink, especially when breaking the fast in the month of Ramadan and to develop entrepreneurial character. The method used the provision of preparation materials for making healthy drink recipes, questions and answers, discussions, practice and mentoring carried out for 24 students of the SMK Kesehatan Surabaya in the classroom and gazebo of the school environment. The result are the service to community through training activities and assistance in making healthy drinks to relieve heartburn getting a positive and enthusiastic response from the participants present.